A rare case of hydrocele in a female - Patil, Prachi Prabhakar; Satia, Meena; Badhwar, V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Vulval swellings have always been a case of a difficult and a puzzling situation and more so when they are huge in size. Vulvar swellings are of various types such as Bartholin cyst, sebaceous cyst, cyst of canal of nuck, inguino-labial hernia and vulval varicosities. Most common vulvar cysts are epidermal inclusion cysts. Usual location is beneath the epidermis. An alternative histogenesis is embryonic remnants or occlusion of pilosebaceous ducts of sweat glands. Cutaneous cysts which are lined by ciliated epithelium are very rare, and authors present a rare case of a cyst arising from a left labium majus resembling a hydrocele seen in males with histopathology suggestive of ciliated cyst of the vulva.